THE ANALYSIS OF TOPICS AND TOPIC BOUNDARY MARKERS IN IONESCO’S ABSURD PLAY THE LESSON - Wijaya, Henny Putri Saking (HUMANIKA, 2018)
People sometimes experience miscommunication when they have a conversation. It may happen because they fail to recognize the topic of discussion and the topic shift markers. A conversation has a clear structure that is not realized by the speakers. In this study, the writer chose The Lesson, one of the most famous absurd plays by Ionesco, as the data. In this play, the structure of conversation is difficult to understand, especially in the conversation between the Professor and the Young Pupil. Based on this condition, the writer investigates the structure of the conversation between the Professor and the Young Pupil in order to find the main topics and the topic boundary markers occurred in the topic shift in the conversation. The data were analyzed using the theories of topic shift by Coulthard (2014) and topic boundary markers by Stenstrom (2014). The findings show that there were four topics in the conversations between the Professor and the Young Pupil and ‘let’s’ is the topic boundary marker often used to open a new topic and to close a topic. In conclusion, even in an absurd play where the structure is difficult to understand, there is a clear structure of the conversation.